Open the door how to excite young people about poetry - Lasky, Dorothea 1978-; Luxford, Dominic; Nathan, Jesse (Poets in the world, 2013)
This mixture of essays, interviews, and lesson plans will prove useful for first-time and veteran teachers, parents, MFA graduates and the like, with an interest in poetry's place in the lives of our younger citizens.